Body mass index-adapted prospective coronary computed tomography angiography: determining the lowest limit for diagnostic purposes - Hosch, Waldemar P.; Hofmann, Nina; Mueller, Dirk; Iwan, Johannes; Gitsioudis, Gitsios; Siebert, Stefan; Giannitsis, Evangelos; Kauczor, Hans-Ulrich; Katus, Hugo; Korosoglou, Grigorios (European journal of radiology, 2013)
Purpose - To investigate the value of 4 different protocols for prospectively triggered 256-slice coronary computed tomography angiography (coronary CTA). - Methods - Two hundred and ten patients underwent prospectively triggered coronary CTA for suspected or known coronary artery disease (CAD). Patients with heart rate >75bps before the scan despite ß-blocker administration and with arrhythmia were excluded. From January to September 2010, 60 patients underwent coronary CTA using a non-tailored protocol (120kV; 200mAs) and served as our ‘control’ group. From September 2010 to April 2012, based on the body mass index (BMI) of the examined patients (BMI subgroups of <25; 25-28; 28-30, and ≥30kg/m2) current tube voltage and tube current were: (1) slightly, (2) moderately or (3) strongly reduced, resulting into the 3 following BMI-adapted acquisition groups: (1) a ‘standard’ (100/120kV; 100-200mAs; n=50), 2) a ‘low dose’ (100/120kV; 75-150mAs; n=50), and 3) an ‘ultra-low dose’ (100/120kV; 50-100mAs; n=50) protocol. - Results - Patients examined using the non-tailored protocol exhibited the highest radiation exposure (3.2±0.4mSv), followed by the standard (1.6±0.7mSv), low-dose (1.2±0.6mSv) and ultra-low dose protocol (0.7±0.3mSv) (radiation savings of 50%, 63% and 78% respectively). Overall image quality was similar with standard dose (1.9±0.6) and low-dose (2.0±0.5) compared to the non-tailored group (1.9±0.5) (p=NS for all). In the ultra-low dose group however, image quality was significant reduced (2.7±0.6), p<0.05 versus all other groups). - Conclusion - Using BMI-adapted low dose acquisitions image quality can be maintained with simultaneous radiation savings of ∼65% (dose of ∼1mSv). This appears to be the lower limit for diagnostic coronary CTA, whereas ultra-low dose acquisitions result in significant image degradation.